Cell signaling during Trypanosoma cruzi invasion - Maeda, Fernando Y.; Cortez, Cristian; Yoshida, Nobuko (Frontiers in Immunology, 2012)
Cell signaling is an essential requirement for mammalian cell invasion by Trypanosoma cruzi. Depending on the parasite strain and the parasite developmental form, distinct signaling pathways may be induced. In this short review, we focus on the data coming from studies with metacyclic trypomastigotes (MT) generated in vitro and tissue culture-derived trypomastigotes (TCT), used as counterparts of insect-borne and bloodstream parasites respectively. During invasion of host cells by MT or TCT, intracellular Ca2+ mobilization and host cell lysosomal exocytosis are triggered. Invasion mediated by MT surface molecule gp82 requires the activation of mammalian target of rapamycin (mTOR), phosphatidylinositol 3-kinase (PI3K) and protein kinase C (PKC) in the host cell, associated with Ca2+-dependent disruption of the actin cytoskeleton. In MT, protein tyrosine kinase (PTK), PI3K, phospholipase C (PLC) and PKC appear to be activated. TCT invasion, on the other hand, does not rely on mTOR activation, rather on target cell PI3K, and may involve the host cell autophagy for parasite internalization. Enzymes, such oligopeptidase B and the major T. cruzi cysteine proteinase cruzipain, have been shown to generate molecules that induce target cell Ca2+ signal. In addition, TCT may trigger host cell responses mediated by TGF-β receptor or integrin family member. Further investigations are needed for a more complete and detailed picture of T. cruzi invasion.